HUBUNGAN BEBERAPA FAKTOR DENGAN PERILAKU SEKSUAL BERISIKO IMS PADA WARIA BINAAN PONDOK PESANTREN (PONPES) WARIA SENIN- KAMIS YOGYAKARTA TAHUN 2015 - Mustafidatun Najah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
International Conference on Population and Development (ICPD) has approved a program of action to ensure sexual health for all, including the prevention of sexually transmitted infections (STIs). In Indonesia the current STI infection rates tend to increase. Based on the results IBBS 2013, the prevalence of syphilis in transsexuals of 9.7% ranks second highest.This study aimed to analyze the relationship between several factors with STI sexual risk behavior on transgenders assisted in Cottage Boarding Senin- Kamis Yogyakarta. This type of research was Explanatory Research with Cross Sectional Study. Population research was 35 transgenders and the sample used is 29 transgenders. Data analysis included univariate, bivariate descriptive (crosstab), analytic bivariate used Chi Square test (Pearson method, Fisher's Exact Test), multivariate analysis (Multiple Logistic Regression). The predictive value of the corelation used a significance level (α = 5%).Results of univariate analysis showed that the highest percentage of respondents that basic education (51.7%), non-PSK jobs (79.3%), poor attitude (58.6%), good availability of health service (55.2%), poor availability of reproductive health education (58.6%), poor health care workers (51.7%), good peers (65.5%) and sexual risk behaviors STI (58.6%). Bivariate analysis showed that there was a corelation between education (pvalue = 0.016), availability health service (pvalue = 0.01), health workers (pvalue = 0.016) with STI sexual risk behavior on transsexuals. Multivariate analysis showed that there was no corelation together between education (pvalue = 0.187), availability of health service (pvalue = 0.122), health workers (pvalue = 0.094) with STI sexual risk behavior.It is suggested to health workers to increase empathy, proactive health information as well as interpersonal communication regularly with groups at risk of STIs.